A New Compact Model for the Avalanche Effect in InAlAs/InGaAs HBTs - Weiß, Oliver; Baureis, Paul; Kellmann, Nikolai; Weber, Norbert; Weigel, Robert (IEEE Electron Device Letters, 2006)
This letter presents a new compact model for the avalanche effect in InAlAs/InGaAs heterojunction bipolar transistors. Unlike previous models, it is based on the formulation of the avalanche multiplication by Lee (Phys. Rev., vol. 134, p. A761, 1964), which allows the model to be valid for even larger current densities than before. The description of the ionization coefficient takes into account the anomaly of the ionization coefficient of InGaAs at low electric fields. The new model is successfully verified by measurements in a conventional common-base setup.
elib2cris::1512001600,weiss2006
Keywords: III-V semiconductors; aluminium compounds; current density; gallium arsenide; heterojunction bipolar transistors; indium compounds; semiconductor device models; InAlAs-InGaAs; avalanche effect; avalanche multiplication; current density; electric fields; heterojunction bipolar transistor; impact ionization; ionization coefficient; Bipolar transistors; Current density; Electrons; Heterojunction bipolar transistors; Impact ionization; Indium compounds; Indium gallium arsenide; Indium phosphide; Optical fiber communication; Wireless communication; Avalanche effect; InGaAs; avalanche multiplication; heterojunction bipolar transistor (HBT); impact ionization; indium phosphide